Organic Solar Cells Based on High Hole Mobility Conjugated Polymer and Nonfullerene Acceptor with Comparable Bandgaps and Suitable Energy Level Offsets Showing Significant Suppression of Jsc–Voc Trade‐Off. Issue 7 (12th May 2019) - Wang, Zhen; Liu, Xuncheng; Jiang, Haiying; Zhou, Xiaobo; Zhang, Lianjie; Pan, Feilong; Qiao, Xianfeng; Ma, Dongge; Ma, Wei; Ding, Liming; Cao, Yong; Chen, Junwu
Abstract : Herein, a high‐mobility polymer (Si25) pairing a nonfullerene acceptor (O‐IDTBR) is introduced to construct active layers of organic solar cells (OSCs). The OSCs based on Si25 and O‐IDTBR with comparable bandgaps of 1.61 eV show high open‐circuit voltage ( V oc ) of 1.03 V. Suitable energy level offsets between the donor and acceptor as well as sufficient photon absorbance by a 400 nm thick active layer afford a notable short‐circuit current ( J sc ) of 21.11 mA cm −2, indicating a significantly suppressed trade‐off between J sc and V oc among OSCs. In addition, notable high power conversion efficiency (PCE) between 10.2% and 11.54% can be achieved with thick blend films from 210 to 560 nm, a thickness range beneficial to pin‐hole free printing. The maximum PCE of 11.54% corresponds to a 400 nm thick blend film, which is a rare thickness for high‐efficiency nonfullerene‐based OSCs. The corresponding fill factors (FFs) are between 51.59% and 53.33%. The inferior FF is due to a very low electron–hole mobility ratio, offering space for future FF elevation. The results highlight the high V oc and J sc potentials for thick‐film nonfullerene OSCs based on a high hole mobility donor as well as looking forward to a high electron mobility nonfullerene acceptor. Abstract : Thick‐film‐induced absorption compensation at short‐wavelength band is designed based on organic donors and acceptors with comparable bandgaps of 1.61 eV and suitable energy offsets for both the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO), giving high J sc and V oc close to perovskite solar cells. As a result, a suppressed trade‐off between J sc and V oc among OSCs is demonstrated.